2018
DOI: 10.3390/ma11071180
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Evaluation of Creep Deformation and Recovery of Bulk-Fill Dental Composites Immersed in Food-Simulating Liquids

Abstract: The aim of this study is to compare the creep/recovery behavior of bulk-fill dental composites after storage in various food simulating organic solvents. For this purpose, five different resin-composites (four bulk-fills and one conventional) were used. A total of 20 rectangular specimens (14 mm × 3 mm × 0.7 mm) were prepared by filling the resin-composites in Teflon mold. All of the specimens for each material (n = 5) were divided into four groups namely dry (control), distilled water (DW), artificial saliva,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
(48 reference statements)
1
12
0
Order By: Relevance
“…Chemical degradation of dental composites after exposure to adverse oral environment especially dietary liquids can remarkably challenge their flexural properties [25]. This is initiated by water absorption that causes dissolution or elution of leachable inorganic filler particles and residual monomers, thus destroying the polymeric network of the material [26]. In addition, leaching of filler particles into oral environment may compromise the biocompatibility of the restorative materials [27].…”
Section: Discussionmentioning
confidence: 99%
“…Chemical degradation of dental composites after exposure to adverse oral environment especially dietary liquids can remarkably challenge their flexural properties [25]. This is initiated by water absorption that causes dissolution or elution of leachable inorganic filler particles and residual monomers, thus destroying the polymeric network of the material [26]. In addition, leaching of filler particles into oral environment may compromise the biocompatibility of the restorative materials [27].…”
Section: Discussionmentioning
confidence: 99%
“…The long-term of such high-performance composites is important to be quantified, given the viscoelastic nature of polymeric matrices (Guedes 2006). A very few studies are found in the literature dealing with the long-term mechanical behavior relating thermoset matrix composites (Sullivan 1990;Sullivan et al 1993;Hu and Sun 2000;Fancey 2001Fancey , 2005Alrahlah et al 2018). Fancey (2001Fancey ( , 2005 mentioned the importance of low-stress creep response for the tensile modulus prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Fancey (2001Fancey ( , 2005 mentioned the importance of low-stress creep response for the tensile modulus prediction. A low-stress level analysis allows a fast and inexpensive way in relation to structure versus property relationship (Alrahlah et al 2018;Fancey 2001Fancey , 2005. General failure mechanisms are present in two main scales, (i) microscopic and (ii) macroscale mechanisms that arise from microstructural changes (Khan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tensile and flexural, 1 interlaminar shear, 2 and crack propagation 3,4 are among the more frequently used tests regarding polymeric composite materials. Other mechanical properties studied are creep, 5,6 recovery, 7,8 and stress relaxation. 9,10 Creep is the permanent deformation in a material when subjected to a constant force or stress, being a function of time.…”
Section: Introductionmentioning
confidence: 99%